Acupuncture protects the interstitial cells of Cajal by regulating miR-222 in a rat model of post-operative ileus. Issue 2 (April 2019) - Deng, Jing-jing; Lai, Ming-yin; Tan, Xinghua; Yuan, Qing
Background: Recovery of the interstitial cells of Cajal (ICCs) during post-operative ileus (POI) is important for the restoration of gastrointestinal (GI) motility. Acupuncture can protect ICCs, but the underlying mechanisms remain unclear. In this study, we investigated whether miR-222, c-kit and endothelial nitric oxide synthase (eNOS) are involved in the putative effects of acupuncture on ICC recovery. Methods: A POI model was established in Sprague-Dawley rats by colo-colic anastomosis, and then acupuncture was performed at bilateral ST36, SP6 and LR3 once daily for 3 consecutive days. C-kit protein expression in the colonic tissue adjacent to the incision site was determined by immunohistochemistry and Western blotting. mRNA levels of c-kit, eNOS and miR-222 were measured by real-time polymerase chain reaction (RT-PCR). Results: The levels of c-kit mRNA/protein and eNOS mRNA decreased, while miR-222 increased in the colonic tissues of POI model rats. Acupuncture treatment improved GI motility, inhibited the up-regulation of miR-222 and blocked the down-regulation of c-kit mRNA/protein and eNOS mRNA. The levels of miR-222 and c-kit were negatively correlated. Conclusion: Acupuncture at ST36, SP6 and LR3 facilitates ICC recovery and improves post-operative GI motility in part through regulation of miR-222, c-kit and eNOS.